Low-noise balanced homodyne detection with superconducting nanowire single-photon detectors - Protte, Maximilian; Schapeler, Timon; Sperling, Jan; Bartley, Tim (Optica Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) have been widely used to study the discrete nature of quantum states of light in the form of photon-counting experiments. We show that SNSPDs can also be used to study continuous variables of optical quantum states by performing homodyne detection at a bandwidth of 400 kHz. By measuring the interference of a continuous-wave field of a local oscillator with the field of the vacuum state using two SNSPDs, we show that the variance of the difference in count rates is linearly proportional to the photon flux of the local oscillator over almost five orders of magnitude. The resulting shot-noise clearance of (46.0 ± 1.1) dB is the highest reported clearance for a balanced optical homodyne detector, demonstrating their potential for measuring highly squeezed states in the continuous-wave regime. In addition, we measured a CMRR = 22.4 dB. From the joint click counting statistics, we also measure the phase-dependent quadrature of a weak coherent state to demonstrate our device’s functionality as a homodyne detector.

Inverses Verfahren zur Identifikation piezoelektrischer Materialparameter unterstützt durch neuronale Netze - Koch, Kevin; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Estimation of temperature-dependent piezoelectric material parameters using ring-shaped specimens - Friesen, Olga; Claes, Leander; Scheidemann, Claus; Feldmann, Nadine; Hemsel, Tobias; Henning, Bernd (2023 International Congress on Ultrasonics, Beijing, China)

Diminishing Domain Mismatch for DNN-Based Acoustic Distance Estimation via Stochastic Room Reverberation Models - Gburrek, Tobias; Meise, Adrian Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (2024 18th International Workshop on Acoustic Signal Enhancement (IWAENC))

Evaluating Supply Scenarios for Hydrogen and Green Fuels from Canada, Chile, and Algeria to Germany via a Techno-Economic Assessment - Seeger, Karl; Genovese, Matteo; Schlüter, Alexander; Kockel, Christina; Corigliano, Orlando; Díaz Canales, Edith Benjamina; Fragiacomo, Petronilla; Praktiknjo, Aaron (United States Association for Energy Economics (USAEE) & International Association for Energy Economics (IAEE) Research Paper Series)

Vorwort - Herzig, Bardo; Eickelmann, Birgit; Schwabl, Franziska; Schulze, Johanna; Niemann, Jan (Lehrkräftebildung in der digitalen Welt Zukunftsorientierte Forschungs- und Praxisperspektiven)

Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven

Methodische Einführung des Konzeptes Messunsicheheiten in der Physik - Sprachliche Analyse von Standardwerken - Bauer, Anna Brigitte (Wissenschaftsdidaktik als kritische Kommunikationsanalyse - Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber)

Empowering Students for the Data-Driven World: A Qualitative Study of the Relevance of Learning about Data-Driven Technologies - Höper, Lukas; Schulte, Carsten (Informatics in Education)
In K-12 computing education, there is a need to identify and teach concepts that are relevant to understanding machine learning technologies. Studies of teaching approaches often evaluate whether students have learned the concepts. However, scant research has examined whether such concepts support understanding digital artefacts from everyday life and developing agency in a digital world. This paper presents a qualitative study that explores students’ perspectives on the relevance of learning concepts of data-driven technologies for navigating the digital world. The underlying approach of the study is data awareness, which aims to support students in understanding and reflecting on such technologies to develop agency in a data-driven world. This approach teaches students an explanatory model encompassing several concepts of the role of data in data-driven technologies. We developed an intervention and conducted retrospective interviews with students. Findings from the analysis of the interviews indicate that students can analyse and understand data-driven technologies from their everyday lives according to the central role of data. In addition, students’ answers revealed four areas of how learning about data-driven technologies becomes relevant to them. The paper concludes with a preliminary model suggesting how computing education can make concepts of data-driven technologies meaningful for students to understand and navigate the digital world.
Keywords: Computer Science Applications; Communication; Education; General Engineering

New Perspectives on the Future of Computing Education: Teaching and Learning Explanatory Models - Höper, Lukas; Schulte, Carsten (Proceedings of the 24th Koli Calling International Conference on Computing Education Research)

Students' Motivation and Intention to Engage with Data-Driven Technologies from a CS Perspective in Everyday Life - Höper, Lukas; Schulte, Carsten; Mühling, Andreas (Proceedings of the 2024 on Innovation and Technology in Computer Science Education V. 1)

Learning an Explanatory Model of Data-Driven Technologies can Lead to Empowered Behavior: A Mixed-Methods Study in K-12 Computing Education - Höper, Lukas; Schulte, Carsten; Mühling, Andreas (Proceedings of the 2024 ACM Conference on International Computing Education Research - Volume 1)

Case study on the software-supported development of competences in Scenario-Technique - Gräßler, Iris; Tusek, Alena Marie (AHFE International)
The content of university teaching in engineering sciences, particularly in product creation, is characterised by the development of application skills. Changing working conditions require new teaching concepts that are oriented towards the needs of students and practice and consider the acquisition of soft skills. A key method to be considered in this context is the Scenario-Technique. In this paper, a one-day workshop based on a software tool for the Scenario-Technique is presented that focusses on competence development for Scenario-Technique in form of a learning concept. Based on a systematic literature analysis, existing approaches for learning the Scenario-Technique are identified and requirements for a subsequently developed software-supported Scenario-Technique workshop are established. Using a case study, the learning concept is validated in two test phases for comprehensibility, user-friendliness, and practical suitability. The result is a concept that enables practice-oriented learning of the Scenario-Technique.

Variations in explainers’ gesture deixis in explanations related to the monitoring of explainees’ understanding - Lazarov, Stefan Teodorov; Grimminger, Angela (Proceedings of the Annual Meeting of the Cognitive Science Society)
In this study on the use of gesture deixis during explanations, a sample of 24 videorecorded dyadic interactions of a board game explanation was analyzed. The relation between the use of gesture deixis by different explainers and their interpretation of explainees' understanding was investigated. In addition, we describe explainers' intra-individual variations related to their interactions with three different explainees consecutively. While we did not find a relation between interpretations of explainees' complete understanding and a decrease in explainers' use of gesture deixis, we demonstrated that the overall use of gesture deixis is related to the process of interactional monitoring and the attendance of a different explainee.
Keywords: explanation; gesture deixis; monitoring; understanding

Were you happy in prison, dear child? Recensie van Maria Kagers 'De buitengewoon geslaagde opvoeding van Frida Wolf' (2024) - Vandenbussche, Saskia (De Reactor. Vlaams-Nederlands platform voor literatuurkritiek)

Handling of uncertainties in the design of sustainable Additive Manufacturing products by merging Design-for-X and Scenario-Technique - Gräßler, Iris; Mozgova, Iryna; Pottebaum, Jens; Ott, Manuel; Jung, Philipp; Hesse, Philipp (17th CIRP Conference on Intelligent Computation in Manufacturing Engineering)
New technologies and materials carry significant potential for sustainable production and use of products. As an example, Additive Manufacturing technologies and materials promise lightweight design and energy efficient use of parts. Exhausting the full potential requires: a) consideration of uncertainties with respect to future capabilities, and b) upgradeable design guidelines to cover advancements consistently. The proposed approach merges concepts of Design-for-X with foresight algorithms of Scenario-Technique to derive actionable knowledge. It is validated by an application in the field of Additive Manufacturing, namely Metal Fused Deposition Modelling. Engineers benefit from the intuitive access to heterogeneous types of sustainability related information.
Keywords: Design-for-X; Scenario-Technique; sustainability; uncertainty; Life-Cycle Engineering; Additive Manufacturing; Circular Economy

Perception and Consideration of the Explainees’ Needs for Satisfying Explanations - Schaffer, Michael Erol; Terfloth, Lutz; Schulte, Carsten; Buhl, Heike M.

Explainers’ Mental Representations of Explainees’ Needs in Everyday Explanations - Schaffer, Michael Erol; Terfloth, Lutz; Schulte, Carsten; Buhl, Heike M. (Joint Proceedings of the xAI-2024 Late-breaking Work, Demos and Doctoral Consortium. 3793)

Hilfst du mir, so hilfst du dir. Diplomatische Überzeugungsstrategien der Regentin Christine Charlotte von Ostfriesland gegenüber Kaiser Leopold I. im 17. Jahrhundert - Becker, Rieke (Österreichische Zeitschrift für Geschichtswissenschaften. Themenband „New Diplomatic History“)
Keywords: New Diplomatic History; Neue Diplomatiegeschichte

Strained Missions: the diplomatic dilemmas of small states from the Global South in the area of autonomous weapons systems - Bhila, Ishmael (Small States & Territories)
Emerging technologies around autonomous weapons systems pose significant threats, particularly to small states in the Global South. Despite these threats, many such small states have struggled to participate in multilateral discussions to regulate and prohibit autonomous weapons systems, while the negotiations have been ongoing within the Group of Governmental Experts on Lethal Autonomous Weapons Systems (GGE on LAWS) under the United Nations Convention on Certain Conventional Weapons (UNCCW) since 2017. This paper analyses the dilemmic positions small state diplomats find themselves in when trying to devote time and expertise to international discussions on autonomous weapons systems while at the same time negotiating the power politics within the international law-making system and working with a limited expertise pool and resource base. The research is based on interviews with diplomats in Geneva, participation data collated by the UN, and virtual and in-person observation of the GGE on LAWS discussions in the UNCCW. The paper concludes that disarmament diplomats from small states from the Global South face various challenges, including small governments back home that cannot address emerging issues, great power politics, unequal international legal systems, and absent common positions on disarmament. Nevertheless, these same small states have dealt with such challenges, so as to decolonise the asymmetric diplomatic space within which they operate.